Grafting with chondroitin sulfate on poly(vinyl alcohol) to improve antifouling property. Issue 1 (14th May 2019) - Zhou, Jinsheng; Lin, Yanming; Lv, Jing; Zhou, Li; Hu, Huiyuan; Yu, Li; Zhang, Qilong; Yang, Hui; Luo, Zhongkuan
Abstract : Poly(vinyl alcohol) (PVA) hydrogels become muddy while used in artificial corneas. To enhance the antifouling property of PVA hydrogels, a PVA hydrogel was grafted with chondroitin sulfate (CdS) through a two-step reaction in this work. The surface chemical compositions, surface morphology and thermal property of the hydrogel were characterized by attenuated total reflectance FTIR, X-ray photoelectron spectroscopy, atomic force microscopy, scanning electron microscopy and thermogravimetric analysis. It was confirmed that CdS was successfully grafted onto the surface of the PVA hydrogel through a two-step method. After grafting with p(GMA-CdS) (GMA: glycidyl methacrylate), both the thermal and mechanical properties of the PVA hydrogel became weaker and the PVA hydrogel became hydrophilic. The biocompatibility of the PVA- g -p(GMA-CdS) hydrogel could be considered as non-cytotoxic according to ISO 10993-5:2009. The antifouling property of the PVA- g -p(GMA-CdS) hydrogel, namely its anti-protein adsorption and anti-cell adhesion, was significantly improved due to surface hydration, steric exclusion effect and charge surface. The anti-protein adsorption of the PVA- g -p(GMA-CdS) hydrogel increased by about 33·48% in comparison with that of the PVA hydrogel and the anti-cell adhesion increased by about 67·92%. Overall, the PVA- g -p(GMA-CdS) hydrogel is an ideal biomaterial candidate for artificial corneas.